Coexistence of iAMP21 and ETV6-RUNX1 fusion in an adolescent with B cell acute lymphoblastic leukemia: literature review of six additional cases. Issue 1 (December 2016) - Gu, Jun; Reynolds, Alexandra; Fang, Lianghua; DeGraffenreid, Corrie; Sterns, Kenneth; Patel, Keyur; Medeiros, L.; Lin, Pei; Lu, Xinyan
Abstract Background Intrachromosomal amplification of chromosome 21 (iAMP21) results from breakage-fusion-bridge cycles and chromothripsis is a distinct marker of a subgroup of B cell acute lymphoblastic leukemia (B-ALL) cases associated with a poor prognosis. iAMP21 accounts for 2% of pediatric B-ALL and occurs predominantly in older children or adolescents.ETV6-RUNX1 fusion, resulting from t(12;21)(p13;q22), is associated with an excellent outcome in younger children with B-ALL. Coexistence of iAMP21 withETV6-RUNX1 fusion is extremely rare with limited clinical information available. Results We report the case of an 18-year old Caucasian man diagnosed withETV6-RUNX1 fusion positive B-ALL. He was treated with intensive chemotherapy and achieved remission for 6 months before relapse, 15 months after the initial diagnosis. G-band karyotyping and Fluorescence in situ hybridization (FISH) analyses performed on bone marrow revealed complex abnormalities: 41, X, -Y, der(3)t(3;20)(p11.2;q11.2), -4, t(5;22)(q32;q11.2), del(9)(p13), dic(9;17)(p13;p11.2), t(12;21)(p13;q22), der(14)t(14;17)(p11.2;q11.2), der(17;22)(q11.2;q11.2), -20, add(21)(q22), -22[4]/46, XY[15] with an iAMP21 and anETV6-RUNX1 . Additional molecular studies confirmedETV6-RUNX1 fusion and with aTP53 mutation. High-resolution single nucleotide polymorphism microarray (SNP array) revealed the iAMP21 to be chromothripsis of 21q and subsequent metaphase FISH further delineated complex genomic aberrations. Although the patient received intensive chemotherapy with allogenic stem cell transplant, he died 26 months after initial diagnosis. We searched the literature and identified six cases showing coexisting iAMP21 andETV6-RUNX1 . The median age for these six patients was 10 years (range, 2–18) and males predominated. The median overall survival (OS) was 28 months. Conclusions Patients with B-ALL associated with both iAMP21 andETV6-RUNX1 tend to be older children or adolescents and have a poor prognosis.